(untitled) (Journal of Parents and Teachers, 2024)
Universal access to culture must include universal access to reading. However, the diverse needs of children and adolescents in our classrooms require adaptations that remove barriers to comprehension. The Easy-to-Read system was developed in response to this challenge. It offers a set of standards, features, and validation processes that modify texts, making them more accessible and understandable to a broader audience.